Dual-Band Antenna System Based on a Metastructure with the Property of an Artificial Magnetic Conductor - Grinev, A. Yu; Izmaylov, A. A. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
The principle of construction and functioning of a combined VHF/UHF antenna system with a frequency ratio of 1:3 is implemented, using a metastructure with the property of an artificial magnetic conductor (artificial magnetic conductor - AMC), which allows to reduce the height of the antenna system's profile and reduce the mutual influence of the bands. An experimental study of the layout of a combined dual-band low-profile antenna system in a single aperture using the principle of electrodynamic similarity was carried out. Dimension in the VHF band (1x2) with printed vibratory emitters, dimension in the UHF band (4x2) based on two-dimensional printed emitters. The measured characteristics (S-parameters, radiation patterns, gain) confirmed the validity of the proposed technical solution of a low-profile antenna system with the preservation of the main ratio technical characteristics. The profile of the combined VHF and UHF antenna system is 62% less compared to the classical case of combined vibratory-vibratory antenna systems.